MANAJEMEN PENDIDIKAN KELUARGA DALAM PERSPEKTIF ISLAM - Heru Gunawan; Zaianal Efendi Hasibuan (Yayasan Baitul Hikmah al-Zain, 2025)
In a family, a child really needs to be well formed physically and psychologically. The family has an important role in shaping a child's character. Even whether a child is safe or unlucky, the family must be responsible both before humans and before God. The family is the organic basis of education for a child's development. So nowadays, many families do not apply the educational values ​​stated in the Al-Qur'an and Hadith. This research uses descriptive qualitative research methods. This research aims to convey to the public the importance of management for the development of family education from an Islamic perspective. This article aims to explore the perspective of the Al-Qur'an and Hadith in managing family education as a whole. The results of the discussion are that the management information system is a large environment that becomes a reference for guidance in family education based on the Qur'an and Al-Hadith